DNA damage response inhibition‐based combination therapies in cancer treatment: Recent advances and future directions. Issue 1 (7th March 2022) - Chen, Tianen; Tongpeng, Suparat; Lu, Ziyi; Topatana, Win; Juengpanich, Sarun; Li, Shijie; Hu, Jiahao; Cao, Jiasheng; Lee, Cheeshin; Tian, Yitong; Chen, Mingyu; Cai, Xiujun
Abstract: DNA molecules are subject to various lesions that can be detrimental to the cells. DNA damage response (DDR) pathways encompass a variety of mechanisms that cells employ in response to DNA damage. While DDR promotes genomic stability in normal cells, it also protects cancer cells from DNA lesions, particularly against exogenous DNA‐damaging agents. Therefore, DDR pathways can be exploited to account for resistance to chemotherapy and radiotherapy and have the potential to be targeted in cancer treatment. Apart from the poly (ADP‐ribose) polymerase (PARP) inhibitors used in BRCA‐mutant cancers, other DDR inhibitors are being developed and tested in clinical trials. Based on the synthetic lethality theory, combination therapies utilizing DDR inhibitors have been explored and are currently undergoing clinical trials, with promising results in cancer treatment. Combination therapies typically employ a DDR inhibitor to sensitize cancer cells to traditional chemotherapeutic agents, radiotherapy, immunotherapy, and even PARP inhibitors. Herein, we focus on recent advances in DDR inhibitor‐based combination therapies other than PARP inhibitors, explore the advantages and disadvantages of the strategies, and discuss the current challenges and future perspectives. Abstract : Cancer cells can survive DNA‐damaging agents via DNA damage response (DDR). Inhibition of DDR sensitizes cancer cells to DNA‐damaging agents, thus overcoming chemo‐ and radio‐resistance.